Perceived ease of use of telehealth services and associated factors in Saudi Arabia: A cross-sectional study - Anis Ben Ghorbal; Ibrahim Elbatal; Abdel-Rahman Aldukeel; Abdelhamid Elshabrawy; Sarah Assem Ibrahim; Niveen Ibrahim Aly El-Zayat; Samah Zakaria; Heba Ahmed Abd El-Wahab; Dina Mohsen Sabry; Thuraya Elsayed; Suzan Abdel-Rahman; Hatem Semary (PLoS ONE, 2025)
This paper aimed to explore the impact of disability along with other factors on telehealth usage, examining the degree of ease people feel while using telehealth services in Saudi Arabia. A cross-sectional study collected data from 428 Saudi adult participants via an online survey between October and November 2024. The Extended Unified Theory of Acceptance and Use of Technology (UTAUT) model was adopted to design the questionnaire. The paper utilized the binary Logistic Regression and the random forest algorithm to predict the participants’ attitudes towards the ease of using Telehealth services. The ease of use of the telehealth system was assessed using the effort expectancy index, which measures participants’ perceptions about feasibility, clarity, simplicity, and comfort related to the usage of telehealth services. The results showed perceptions supporting the ease of using telehealth services decreased for disabled individuals by 80% (p = 0.04) compared to non-disabled individuals. In contrast, availability of facilitating conditions (OR=9.18, p < 0.001), performance expectancy (OR=4.70, p = 0.006), perceived safety (OR=3.33, p = 0.044), and social influence (OR=3.82, p = 0.016) were positively and significantly associated with perceived ease of use. The presence of perceived barriers also had a positive effect (OR=3.62, p = 0.024). The random forest algorithm outperformed logistic regression in terms of classification accuracy and AUC (0.774 versus 0.758 in the test set). Classification models indicated that factors related to telehealth technology were the most influential in perceptions of ease of use. These findings underscore the need for policymakers to develop inclusive telehealth strategies that specifically address barriers faced by disabled individuals, ensuring equitable and accessible digital health services for all.